Piperine as a Potential Anti-cancer Agent: A Review on Preclinical Studies - Manayi, Azadeh; Nabavi, Seyed M.; Setzer, William N.; Jafari, Samineh (Current Medicinal Chemistry, 2018)
Recently many studies showed anticancer activities of piperine, a pungent alkaloid found in black pepper and some other Piper species. We attempted to summarize acquired data that support anticancer potential of this natural agent. Piperine has been reported to possess effective chemopreventive activity. It has been studied to affect via several mechanisms of action, in brief enhancing antioxidant system, increasing level and activity of detoxifying enzymes and suppressing stem cell self-renewal. Moreover, piperine has been found to inhibit proliferation and survival of various cancerous cell lines via modulating cell cycle progression and exhibiting anti-apoptotic activity, respectively. This compound has been shown to modify activity of various enzymes and transcription factors to inhibit invasion, metastasis and angiogenesis. Interestingly, piperine has exhibited antimutagenic activity and also inhibited activity and expression of multidrug resistance transporters such as P-gp and MRP-1. Besides, about all reviewed studies have reported selective cytotoxic activity of piperine on cancerous cells in compared with normal cells. Altogether, the studies completely underline promising candidacy of piperine for further development. The collected preclinical data we provided in this article can be useful in the design of future researches especially clinical trials with piperine.
Keywords: Alkaloid